Effect of Al₂O₃–SiO₂ Composites on the Breakdown Voltage and Physicochemical Properties of Palm-Based Transformer Oil - Athala Kevin B. G. Maturbongs; Zainal Alim Mas'ud; Mohammad Khotib; Roza Indra Laksmana (Jurnal Kimia Sains dan Aplikasi, 2025)
Mineral oil is a type of transformer oil commonly used as a coolant and electrical insulator, playing a vital role in transformer performance. However, its low biodegradability and environmental toxicity have prompted research into alternative materials. Palm oil has emerged as a promising substitute due to its biodegradability, favorable electrical properties, and abundance. This study aims to evaluate the effect of Al₂O₃–SiO₂ particles on the breakdown voltage (BDV) of palm oil as transformer oil. The particles were synthesized using the sol-gel method and characterized by FTIR, XRD, PSA, and SEM. They were then dispersed into palm oil at a concentration of 0.5 g/L. The BDV performance of Al₂O₃–SiO₂ was compared with that of single-component particles (Al₂O₃ and SiO₂) to assess their differences. In addition to BDV, other parameters—including color scale, total acid number, density, kinematic viscosity, and functional groups—were analyzed and compared to the quality standards specified in ASTM D6871-17 and IEC 62270:2018. The results showed that Al₂O₃–SiO₂ particles yielded higher BDV, moisture content, density, and viscosity, but a lower acid number in palm oil compared to single-component particles. Overall, palm oil with dispersed particles met the required quality standards for use as transformer oil.